Gender-sensitive and youth-friendly physiotherapy: Steps toward a stress management intervention for girls and young women. (2nd January 2016) - Strömbäck, Maria; Wiklund, Maria; Salander Renberg, Ellinor; Malmgren-Olsson, Eva-Britt
ABSTRACT: This article describes and evaluates initial steps of a gender-sensitive, youth-friendly group intervention model designed for teenage girls and young women who experience stress-related or psychosomatic problems. Fifty-four young women (16–25 years of age) participated in a gender-sensitive physiotherapy stress management course at a youth health center. Inclusion criteria were self-defined stress-related problems and a wish to participate in the group intervention. Measurements of aspects of body perception, self-image, multiple somatic problems, and mental health symptom areas were assessed both before and after intervention with the Body Perception Questionnaire ad modum Schiöler, social analysis of social behavior, and Adult Self-Report scale. Significant positive changes were found in aspects of body perception, self-image, and mental health and somatic symptoms. The changes were most significant in lower internalization of anxiety and depression symptoms. Symptoms such as headaches and sleeping problems decreased. Participants were more satisfied with their bodies and more able to listen to body signals. Among cognitive issues, significant change occurred in thought problems, but not in attention problems. The intervention model needs further evaluation in controlled trials, but is promising and should be developed further in other physiotherapy settings and subgroups of young people.